Gun shot of the spine Surgical out come and prognosis - AL-Shalchy, Ali K. (Journal of the Faculty of Medicine Baghdad, 2008)
Background: the management of gun shoot wounds of the spinal cords (G sws) is still a debate whether to interfere surgically or not, the interferance is usually laminectomy & Bullet extraction. Objectives: A comparative prospective study between surgical & non-surgical management of G sws. Methods: A case series study of (52) patients with G sws were managed by the neurosurgical unit in Ibn Sinna hospital in Mosul. 27 patients surgery was done, 25 patients non-surgical management. A comparative study done according to the surgical outcome, improvement, mortality between the 2 groups in a mean follow up period of 4.5 months. Results: The mean age was 35, (9-50 years) , mean follow up 4.5 months (3-7 months)no patients with non-surgical treatment show any improvement while 10 out 13 of incomplete injury show significant improvement by surgery, the mortality rate was also higher in the nonsurgical group. Conclusion:Bullet in the spinal cord with partial injury of the cord should be removed with decompression of the cord complete injury of the cord show poor prognosis with or without surgical intervention.